Enhancing kindergarten children gross motor skills through clogs: An Indonesian traditional games - Rahmat, M. Yusran; Akib, Tasrif; Anggraini, Kiki Rizki (Universitas Ahmad Dahlan, 2024)
Gross motor development is a critical aspect of early childhood education, enabling children to build coordination, balance, and body strength. This study aimed to improve children’s gross motor skills through the implementation of clogs (bakiak) traditional games in Aisyiyah Bustanul Athfal III Paranga Kindergarten, Gowa Regency. Using classroom action research conducted in two cycles, the study involved nine boys aged 5–6 years as participants. Data were collected through observation and performance assessments and analyzed descriptively. The results showed a significant improvement in gross motor skills, with the percentage of children achieving the expected developmental level increasing from 27.08% in the pre-cycle to 62.5% in cycle I, and 93.05% in cycle II. These findings indicate that clogs traditional games provide effective, culturally relevant, and engaging activities for enhancing young children’s gross motor development. The study contributes practical insights for integrating local traditional games into early childhood education settings.